2004
DOI: 10.1116/1.1640399
|View full text |Cite
|
Sign up to set email alerts
|

Selective growth of carbon nanotube on scanning probe tips by microwave plasma chemical vapor deposition

Abstract: We have selectively grown carbon nanotubes on the probe tip of an atomic force microscope by microwave plasma chemical vapor deposition. The catalyst domain was defined on the tip apex of an Si based scanning probe by local electric field induced oxidation of a TiN cap layer, under which the cobalt catalyst layer was predeposited on the probe surface. High resolution atomic force microscopy images of an SiO2 trench pattern are demonstrated using the carbon nanotube tip. The nanotube tip fabrication method is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In place, growth of CNT was observed only at the root of metal tip. This tendency is basically similar to that reported by Pan, et al [14] and Yoshimura, et al [15]. Since the ion flux at the tip apex is higher than that at the root due to different electric field concentration, Fe catalyst would be sputtered away preferentially from the tip apex by the ion bombardment.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In place, growth of CNT was observed only at the root of metal tip. This tendency is basically similar to that reported by Pan, et al [14] and Yoshimura, et al [15]. Since the ion flux at the tip apex is higher than that at the root due to different electric field concentration, Fe catalyst would be sputtered away preferentially from the tip apex by the ion bombardment.…”
Section: Resultssupporting
confidence: 89%
“…The conductive CNT probes would be useful in a multiprobe microscope [9]. Several fabrication methods of CNT tips have previously been demonstrated, for example, manual attachment of a CNT to the tip apex using an acrylic adhesive [2], electron beam induced deposition (EBID) of amorphous carbon under scanning electron microscope (SEM) [10], and direct growth by a chemical vapor deposition (CVD) technique [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is demonstrated that the CNTs are suitable as tips of atomic force microscopy (AFM) [2][3][4] and scanning tunneling microscopy (STM) [5,6]. Numerous methods to make CNTs tips have been reported: manual attachment of CNTs to the tip apex using an acrylic adhesive [2], electron beam-induced deposition (EBID) of amorphous carbon under SEM [7], and direct growth by a chemical vapor deposition (CVD) technique [8][9][10][11][12]. The CVD technique is most preferred in terms of mass production in the commercial use.…”
Section: Introductionmentioning
confidence: 99%